NEEM, Azadirachta indica L. (A. Juss): AN ECO-FRIENDLY BOTANICAL INSECTICIDE FOR MANAGING FARMERS’ INSECTS PEST PROBLEMS - A REVIEW (FUDMA JOURNAL OF SCIENCES, 2021)
The search for reducing risks associated with the use of chemicals has necessitated use of pest control using plant products. Neem is perhaps one of the most useful medicinal plant in the tropics. Each part of the tree has huge insecticidal property. Apart from the chemistry of the neem compounds, considerable progress has been achieved regarding the biological activity and insecticidal uses of neem. It is now considered as a valuable source of unique natural product for botanical insecticides against various pests. Farmers in tropical countries commonly used its leaves, seed kernels and its oil in various forms. Neem is utilized in form of powders, extracts or as an emulsifiable oil. Researches had shown that neem consists of pesticidal ingredients called triterpenes (limonoids). Trials conducted on the effect of neem products revealed secondary metabolites affect metabolic processes that include feeding and oviposition deterrence; metamorphosis inhibition, protein synthesis, changes in biological fitness, impaired sexual communication and chitin synthesis. Azadirachtin in particular interferes with chemoreception and exerts direct negative effects on many insect tissues such as muscles and digestive epithelial cells as well as insect mortality. Neem derived biopesticides are cheap, available in all ecological zone, posed no hazard to applicator and the environment as it is biodegradable. Insects such as Aphids, African migratory locust, legume pod-borer, coreid bugs and storage insect pests such as cowpea seed bruchid were controlled using neem. Sustainable insect pest control can be achieved with the use of neem based biopesticides.
Keywords: Neem, Azadirachta indica, eco-friendly, managing, pest, problems